An Elementary History of English (fascicle three) - Marino Castrillón (Ikala: Revista de Lenguaje y Cultura, 1998)
With this third and last chapter of An Elementary History of English, M. Castrill6n doses his 'humble opusailum*. This section develops two important influences on Old English: On one hand, a new Latin influence with the christianization of Britain, on the other, the Scandinavian influence with the Norsemen's expansionists and conquering movements.